Uremic Cardiomyopathy: A New Piece in the Chronic Kidney Disease-Mineral and Bone Disorder Puzzle - de Albuquerque Suassuna, Paulo G.; Sanders-Pinheiro, Helady; de Paula, Rogério B. (Frontiers in Medicine, 2018)
Cardiovascular diseases are the main cause of death in chronic kidney disease (CKD) patients. In dialysis patients, sudden cardiac death accounts for 40% of all deaths. In these patients, sudden cardiac death is usually secondary to an underlying cardiomyopathy, which is clinically identified by the high prevalence of left ventricular hypertrophy and the resultant mechanical and electrical dysfunction. CKD-related cardiomyopathy has a multifactorial pathophysiology. Recent evidence has highlighted the central pathophysiological role of chronic kidney disease-mineral and bone disorder (CKD-MBD) with hyperphosphatemia and high fibroblast growth factor 23 (FGF23) levels in these patients. Further, since CKD is known to be an αKlotho deficiency state, experimental studies have demonstrated that the deleterious effects of FGF23 can be minimized by reestablishing adequate soluble Klotho levels. Herein, we present a review that addresses not only the development of the understanding of CKD-related cardiomyopathy pathophysiology, but also explores the recent data that identify the triad of hyperphosphatemia, high FGF23 levels and αKlotho deficiency as playing a central role on it. Taken together, the data suggest that the uremic cardiomyopathy can be considered a new piece in the CKD-DMO puzzle.